Strategi Pemecahan Masalah Matematika Siswa SMP Ditinjau dari Gaya Kognitif - Ningtiyas, Niken Ayu; Masriyah, Masriyah (Universitas Negeri Surabaya, 2024)
Mathematical problem solving strategy is a method used in the problem solving process to find solutions to mathematical problems. Cognitive styles that are classified based on how to choose a problem solving strategy are field dependent and field independent cognitive styles. The use of various strategies can be seen in the application of mathematical problems. To find out the strategy of solving math problems, indicators can be shown about various strategies for solving math problems, they are: (1) working backward; (2) look for pattern; (3) adopting a different point of view; (4) solving a simpler analogous problem; (5) draw a picture and model; (6) guess and check; (7) organizing data; (8) logical reasoning; and (9) write an equation. The purpose of this study was to describe the math problem solving strategies of students with field dependent and field independent cognitive styles. This research is included in qualitative descriptive research. The subjects of this study were two students with field dependent and field independent cognitive styles who had been taught quadrilateral and triangle material. This study uses instruments in the form of GEFT tests, math ability tests, problem solving tasks, and interview guidelines. The data obtained were then analyzed by reducing data, presenting data, and drawing conclusions. The results of this study indicate that, 1) students with field dependent cognitive style in solving mathematical problems using the strategy of logical reasoning, working backwards, write an equation and organizing data. 2) Students with field independent cognitive style in solving math problems using the strategy of adopting a different point of view, look for pattern, doing logical reasoning, write an equation, draw a picture and model, and guess and check. Problem solving strategies used by FI students are more varied than FD students.